A trip to healthcare - david matz (The Beryl Institute, 2017)
This narrative shares how my experience with two colonoscopies and three surgeries in one year taught me that I am not so good at engaging in treatment decisions. I thought I was. This essay sets out where I made my mistakes, why I believe I made those mistakes, and how the hospitals, intentionally or not, made good decision-making harder. I offer two suggestions for enhancing the role of the patient in decision-making including 1) Every doctor in a diagnostic-decision-making interview should use the sentence “You have some choices here.” The doctor will have preferences, of course, but the patient needs to hear that there is more than one way to take the next step and 2) For diagnostic-decision-making moments, all doctors (and hospitals) should provide patients with support personnel to help the patients use decision-aids, prepare for discussions with doctors, and make the decisions. I conclude with why this is critical in healthcare today.